La Californie : axis du basculement des États-Unis vers un monde pacifico-centré - Frédéric Leriche (L'Espace Politique)
The paper aims at showing that California is both a spatial interface between the United States and the Asian world, and a temporal interface between the USA of yesterday oriented towards an Atlantico-centric world and the USA of tomorrow oriented towards a Pacifico-centric world. We argue that California is an axis allowing the USA as a global power to manage the swinging of the world as a progressive and positive transformation rather than as a destructive crisis that would damage its global position. We begin by analysing the rise of a Pacifico-centric world, in order to understand how it impacts California. We then highlight the main principles of US foreign policy, regarding the rise of such a new Pacifico-centric world. We finally show how California is indeed a tool of US foreign policy in the Asian-Pacific region.